Growth and Biomass Production of Moringa Cultivated in Semiarid Region as Responses to Row Spacing and Cuts - R. S. Santos; J. V. Emerenciano Neto; B. R. S. Bonfim; G. S. Difante; J. D. V. Bezerra; F. N. Lista; A. L. C. Gurgel; M. G. S. Bezerra (Tropical Animal Science Journal, 2021)
The management of the moringa to produce biomass, as it is for other vegetal species, must consider some aspects that foster productivity. Among these aspects, cultivation density is a crucial element. This research aimed to assess the effects of spacing and cuts on the growth of the moringa. The treatments consisted of four spacings: 0.5 x 1.0 m; 0.83 x 1.0 m; 1.25 x 1.0 m; and 1.66 x 1.0 m. The experimental design was a randomized-block design with five repetitions. The standardization cut of the plants was performed at a one-meter height from the ground, fifty days after the seedlings transplantation. The assessments were performed every sixty days, totaling six cuts. Spacing impacted the growth and biomass production but did not affect the height of the plants. The stem diameter, branch number, and the plant’s mass increased at increasing the spacing. On the other side, the total mass and the masses of the stem, the leaflet, and the petiole per hectare decreased at increasing the spacing. Spacing did not affect the ratio between leaf/stem and leaflet/petiole. Plant growth and dry matter production were highest after the first two cuts and decreased significantly from the third cut on. The spacing of 0.5 x 1.0 m should be used for planting Moringa oleifera Lam. because this configuration, even reducing the gain per plant, increased the production of dry matter per unit area.